SF3b4: A Versatile Player in Eukaryotic Cells - Xiong, Feng; Li, Sha (Frontiers in Cell and Developmental Biology, 2020)
Spliceosomes are large protein-RNA complexes regulating pre-mRNA processing in eukaryotes. SF3b4 encodes a core subunit of the U2-type spliceosome, loss- or gain-of-function of which often associates with abnormal cell growth, leading to tumorigenesis. Homologs of SF3b4 in other phyla are also essential. In this review, we summarize recent findings on the function of SF3b4. Importantly, we highlight the versatile roles of SF3b4, not only as a component for pre-mRNA splicing, but also as a regulator for transcription, translation, and cell signaling. Recent studies of SF3b4 in different species across evolution will facilitate a better understanding of human diseases caused by the malfunction of SF3b4, such as Nager syndrome and cancer, in the future.